2018
DOI: 10.4149/neo_2018_170206n77
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 expression can be regarded as prognostic factor for survival of non-small cell lung cancer patients after chemoradiotherapy

Abstract: Inoperable locally advanced non-small cell lung cancer (LA NSCLC) is treated with concurrent or sequential chemotherapy (ChT) and radiation therapy (RT). Survival rates with this treatment remains poor, reported 5-year survival is about 15%. New treatment strategies, including immunotherapy with programmed death ligand-1 (PD-L1) check point inhibitors are being investigated. The clinical significance of PD-L1 expression in tumor samples from patients with inoperable LA NSCLC who underwent concurrent chemoradio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 22 publications
1
18
0
1
Order By: Relevance
“…The objective of present analysis was the confirmation of our previously published data about prognostic value of PD-L1 expression on survival of patients with unresectable NSCLC in stage III that were treated with definitive combined RT and ChT [ 11 ]. In present retrospective analysis, we found no difference between PFS and OS of patients with NSCLC neither in group of ≥ 1% nor in ≥ 50% PD-L1 expression.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…The objective of present analysis was the confirmation of our previously published data about prognostic value of PD-L1 expression on survival of patients with unresectable NSCLC in stage III that were treated with definitive combined RT and ChT [ 11 ]. In present retrospective analysis, we found no difference between PFS and OS of patients with NSCLC neither in group of ≥ 1% nor in ≥ 50% PD-L1 expression.…”
Section: Discussionmentioning
confidence: 58%
“…Expression of PD-L1 on tumor cells is one of the most investigated predictors of benefit from immune checkpoint blockade in advanced NSCLC but little is known about the association of PD-L1 expression and clinicopathological parameters including prognosis of patients with unresectable stage III NSCLC [ 6 10 ]. In our previous research, we assessed the impact of PD-L1 expression on tumor cells from patients with unresectable stage III NSCLC who were treated in our institution between 2005 and 2010 in prospective trial with concurrent chemotherapy (ChT) and radiotherapy (RT) [ 11 ]. We found significant shorter progression free survival (PFS) and overall survival (OS) in patients with PD-L1 expression.…”
Section: Introductionmentioning
confidence: 99%
“…Ventana monoclonal antibody and an automated staining platform was used as described in our previous report. 14 …”
Section: Methodsmentioning
confidence: 99%
“…Expression of PD-L1 is the most studied predictor biomarker for anti-PD-L1 therapy. 35 , 36 , 37 Trials with pembrolizumab demonstrated improved outcomes in metastatic NSCLC patients with PD-L1 expression ≥ 50%. 23 , 25 Three patients in our review with symptomatic pseudoprogression that were treated with pembrolizumab had PD-L1 expression over 50%.…”
Section: Discussionmentioning
confidence: 99%